A Late Eocene date for Late Triassic bird tracks - Melchor, Ricardo Nestor (2013)
Bird-like tracks from northwest Argentina have been reported as being of Late Triassic age1. They were attributed to an unknown group of theropods showing some avian characters. However, we believe that these tracks are of Late Eocene age on the basis of a new weighted mean 206Pb/238U date (isotope dilution–thermal ionization mass spectrometry method) on zircons from a tuff bed in the sedimentary succession containing the fossil tracks. In consequence, the mentioned tracks are assigned to birds and its occurrence matches the known fossil record of Aves.